The Mediating Role of Attitude Toward Money on Students’ Financial Literacy and Financial Behavior - Nurdian Susilowati; Kardiyem Kardiyem; Lyna Latifah (Universitas Negeri Malang, 2020)
This research aims at discovering the direct influence of financial literacy on financial behavior; finding out the indirect influence of financial literacy on financial behavior through attitude toward money; and figuring out the direct influence of attitude toward money on financial behavior. This research was conducted at Economics Faculty of State University of Semarang or UNNES with its sample being students who had taken budgeting and financial management courses. The sample was taken using proportionate random sampling and 230 respondents were obtained. The data were collected using questionnaire and they were then analyzed using descriptive analysis and path analysis. Based on the first research result, it was found that financial literacy had direct influence on financial behavior. High financial literacy determined a good financial behavior in the future. Secondly, attitude toward money successfully mediated the influence of financial literacy on students’ financial behavior. Thirdly, attitude toward money has a direct influence on financial behavior. In general, students have good financial literacy, attitude towards money, and financial behavior. This allowed them to have a clear priority for their future.